2005
DOI: 10.1038/sj.emboj.7600618
|View full text |Cite
|
Sign up to set email alerts
|

Leucyl-tRNA synthetase from the ancestral bacterium Aquifex aeolicus contains relics of synthetase evolution

Abstract: The editing reactions catalyzed by aminoacyl-tRNA synthetases are critical for the faithful protein synthesis by correcting misactivated amino acids and misaminoacylated tRNAs. We report that the isolated editing domain of leucyl-tRNA synthetase from the deep-rooted bacterium Aquifex aeolicus (alphabeta-LeuRS) catalyzes the hydrolytic editing of both mischarged tRNA(Leu) and minihelix(Leu). Within the domain, we have identified a crucial 20-amino-acid peptide that confers editing capacity when transplanted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 65 publications
3
78
2
Order By: Relevance
“…The first coarse sieve, an aminoacylation active site that is located in an ancient canonical core of the aaRS, is responsible for activating amino acids. A second fine sieve, a hydrolytic active site, has been clearly demonstrated to correct the enzyme's mistakes in a number of synthetase systems (27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introduction: Aminoacyl-trna Synthetase Fidelitymentioning
confidence: 99%
“…The first coarse sieve, an aminoacylation active site that is located in an ancient canonical core of the aaRS, is responsible for activating amino acids. A second fine sieve, a hydrolytic active site, has been clearly demonstrated to correct the enzyme's mistakes in a number of synthetase systems (27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introduction: Aminoacyl-trna Synthetase Fidelitymentioning
confidence: 99%
“…Examination of the IleRS, ValRS, and LeuRS CP1 domains as free-standing fragments showed that they possess hydrolytic activity toward misacylated tRNA (11)(12)(13). Analogs of misacylated tRNA were shown to bind to a threonine-rich cleft in the CP1 domains of IleRS and LeuRS, uncovering a proofreading site located 30 Å away from the synthetic site (14,15) and pinpointing specific amino acid residues that may participate in post-transfer editing.…”
mentioning
confidence: 99%
“…91 Proofreading to remove amino acids from noncognate tRNAs was likely to have been as necessary for A73 tRNAs as it is for A76 tRNAs. Given the abilities of separately expressed editing domains to deacylate A76 tRNAs, 152,153 and the existence of separate proteins for trans-editing in some cases, 92,93,137 similar editing proteins may have served the same purpose for A73 tRNAs. Hence, editing domains in aaRSs may have been carried over from the A73 tRNA period.…”
Section: Evolution Of Trnasmentioning
confidence: 99%